An example of a complete orthonormal system in a Hilbert space of generalized functions - Gladkivs’ka, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We construct a complete orthonormal system of generalized functions in a Hilbert space W −1. We obtain an estimate of the error of approximation in W −1, which is expressed in terms of the integral modulus of continuity of a function from L 2.